1996
DOI: 10.1046/j.1365-2567.1996.d01-781.x
|View full text |Cite
|
Sign up to set email alerts
|

3‐deazaadenosine analogues inhibit the production of tumour necrosis factor‐α in RAW264.7 cells stimulated with lipopolysaccharide

Abstract: SUMMARYThe effects of 3-deazaadenosine (DZA), 3-deaza(Ϯ)-aristeromycin (DZAri) and 3-deazaneplanocin (DZNep) on tumour necrosis factor-␣ (TNF-␣) production were examined in the mouse macrophage cell line, RAW264.7, stimulated with lipopolysaccharide (LPS). The 3-deazaadenosine analogues inhibited the TNF-␣ production and the inhibition was dependent upon the concentration of the analogue. DZA reduced the level of TNF-␣ mRNA suggesting that DZA acts at a transcriptional step. In contrast, DZAri and DZNep had li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Interestingly, others have shown that several inhibitors of SAH hydrolase also inhibit LPS-induced TNF␣ expression. 38 These observations led us to examine the effect of SAH on LPS-induced TNF␣ and iNOS expression. Similar to SAMe and MTA, SAH pretreatment significantly inhibited the ability of LPS to increase TNF␣ and iNOS mRNA levels.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, others have shown that several inhibitors of SAH hydrolase also inhibit LPS-induced TNF␣ expression. 38 These observations led us to examine the effect of SAH on LPS-induced TNF␣ and iNOS expression. Similar to SAMe and MTA, SAH pretreatment significantly inhibited the ability of LPS to increase TNF␣ and iNOS mRNA levels.…”
Section: Discussionmentioning
confidence: 99%
“…Most changes are immunosuppressive in nature; some may be mediated through changes in NF-kB activity (Jeong et al, 1999). Thus, several compounds reduced the production of TNF-a by endotoxin-treated macrophages and protected mice against endotoxin challenge (Parmely et al, 1993;Jeong et al, 1996). Adenosine analogs also inhibited the activation of T cells and decreased the phagocytic activity of macrophages (Sung and Silverstein, 1985;Wolos et al, 1993a,b;Lambert et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Because DZA is also able to serve as a substrate for Ado-Hcy hydrolase, the interaction between DZA and Ado-Hcy hydrolase results in the accumulation of 3-deazaadenosylhomocysteine (DZAHcy) in cultured cells [2] and the liver [3]. It is also well known that DZA exerts a wide variety of biological functions such as anti-human immunodeficiency virus (HIV) activity [4], anti-inflammatory effects [5], alterations in the expression of genes like collagen IV and ICAM-1 [6,7], the inhibition of TNF-α and IL-1β expression [8], and an inhibitory effect on nuclear NF-κB transcriptional activity [9]. In addition, DZA has been reported to induce apoptosis in human and murine leukemic cell lines such as HL-60, U937 and L1210 cells [10][11][12].…”
Section: Introductionmentioning
confidence: 99%